2022
DOI: 10.1101/2022.08.12.503723
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionary dynamics of genome size and content during the adaptive radiation of Heliconiini butterflies

Abstract: Heliconius butterflies, a speciose genus of Mullerian mimics, represent a classic example of an adaptive radiation involving a range of derived dietary, life history, physiological and neural traits. However, key lineages within the genus, and across the broader Heliconiini tribe, lack genomic resources, contrasting our understanding of how adaptive and neutral processes shaped genome evolution across their radiation. Here, we build new, highly-contiguous genome assemblies for nine new Heliconiini, reference-a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 163 publications
(155 reference statements)
2
17
0
Order By: Relevance
“…A similar distinction between the autosome-majority trees and the Z-chromosome tree was also found by Zhang et al (2016). All four scenarios a-d confirm paraphyly of the silvaniform species (H. besckei, H. numata and the pardalinus-hecale clade), consistent with some recent phylogenomic studies (Zhang et al 2016;Massardo et al 2020;Cicconardi et al 2023). Monophyly of the silvaniforms was suggested in concatenation/sliding-window analysis (Heliconius Genome Consortium 2012; Kozak et al 2015;Kozak et al 2021;Zhang et al 2021), but this conclusion may suffer from a failure to account for deep coalescence (Edwards et al 2016).…”
Section: Major Introgression Patterns In the Melpomene-silvaniform Cladesupporting
confidence: 86%
See 1 more Smart Citation
“…A similar distinction between the autosome-majority trees and the Z-chromosome tree was also found by Zhang et al (2016). All four scenarios a-d confirm paraphyly of the silvaniform species (H. besckei, H. numata and the pardalinus-hecale clade), consistent with some recent phylogenomic studies (Zhang et al 2016;Massardo et al 2020;Cicconardi et al 2023). Monophyly of the silvaniforms was suggested in concatenation/sliding-window analysis (Heliconius Genome Consortium 2012; Kozak et al 2015;Kozak et al 2021;Zhang et al 2021), but this conclusion may suffer from a failure to account for deep coalescence (Edwards et al 2016).…”
Section: Major Introgression Patterns In the Melpomene-silvaniform Cladesupporting
confidence: 86%
“…We next focus more closely on the melpomene-silvaniform clade (including H. besckei, H. numata and H. melpomene, represented by "BNM" in Figure 1A), one of the most phylogenetically difficult groups of Heliconius due to ongoing hybridization and extensive gene flow involving most members of the group (Mallet et al 2007). Previous studies have inferred conflicting introgression scenarios in this clade (Martin et al 2013;Zhang et al 2016;Jay et al 2018;Edelman et al 2019;Cicconardi et al 2023). We compiled a multilocus dataset from high-quality genome data comprising 8 (out of 15) species representing all major lineages within the clade: H. melpomene, H.…”
Section: Major Introgression Patterns In the Melpomene-silvaniform Cladementioning
confidence: 99%
“…All phylogenetic comparative analyses were conducted using a new phylogenetic tree of the Heliconiini generated from newly assembled genomes (6). To assemble additional genomes of Heliconius erato cyrbia , H. melpomene rosina , H. m. amaryllis , and H. cydno galanthus , short-read illumina data was downloaded from NCBI (National Centre for Biotechnology Information) and a reference-guided assembly approach adapted and extended from Lischer and Shimizu (7) adopted.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…As already discussed, access to pollen would become crucial at later stages of adulthood, but the remaining question is: where did the valine and isoleucine used for CG biosynthesis come from during the first weeks of Heliconius adulthood in the control group (sugar only)? A recent comparative genomic study has found that two hexamerins, storage proteins, have been duplicated multiple times in heliconiines (Cicconardi et al, 2022). Hexamerins might provide valine and isoleucine for CG biosynthesis during the beginning of their adulthood, if pollen is not available.…”
Section: Discussionmentioning
confidence: 99%
“…Cocoonases are used by moths for cocoon digestion during eclosion and moths contain only a single copy of this enzyme, while Heliconius have multiple copies (Harpel et al 2015; Smith et al 2018). Nonetheless, comparative genomics has shown that they are duplicated in all heliconiines, even those that do not pollen feed (Cicconardi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%